Spatial and sociodemographic factors associated with surgical site infection rates in hospitals in inner São Paulo State, Brazil. (February 2021) - Carvalho, A.G.M.L.; Limaylla, D.C.; Vilches, T.N.; de Almeida, G.B.; Madalosso, G.; de Assis, D.B.; Fortaleza, C.M.C.B.
Summary: Low-to-middle-income countries often have high incidence of surgical site infection (SSI). To assess spatial and sociodemographic predictors of SSI rates, this study analysed and georeferenced governmental surveillance data from 385 hospitals located in inner São Paulo State, Brazil. In multi-variate models, SSI rates were positively associated with distance from the state capital [incidence rate ratio (IRR) for each 100 km 1.19, 95% confidence interval (CI) 1.07–1.32], and were lower for non-profit (IRR 0.95, 95% CI 0.37–0.85) and private (IRR 0.47, 95% CI 0.31–0.71) facilities compared with public hospitals. Georeferencing results reinforced the need to direct SSI-prevention policies to hospitals located in areas distant from the state capital.